Case report of atypical osteonecrosis of the jaws: a clinical dilemma. Issue 4 (May 2019) - Johnson King, O.; Halai, T.; Eyeson, J.
Abstract: Osteonecrosis of the jaws is defined as exposed jawbone that persists for more than eight weeks. Treatment may be challenging and can adversely affect the patient's quality of life. We present a male patient who was referred to our department with areas of extensive osteonecrosis in the maxilla and mandible. He had no history of antiresorptive, antiangiogenic treatments, or radiotherapy to the head and neck. He had a history of renal transplantation, diabetes, glucocorticoids, and periodontal disease. This case highlights multiple aetiological factors that can contribute to osteonecrosis and the diagnostic dilemma that they may cause.